(3GdGfJUGQ dSeGY GdMLGQs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdGfJUGQ ef Phi dLeGd GdBKGQ GdfHhjI hGdSff CeG HYO aGf Gddg YR hLd edg GdaVd hGdefI GcQe gPg GdCeI GdeMeOjI s
(3BNQgG (B:s
(3dCf GHQGgje GdePchQ ajeG fYde ef GdCeQ GdeTghQ BNQ ef Hbi ai GdCbWGQ aef CLGR dg NGUkG GdMLGQ hjPcQg NJeG gPG GdeDda GdeSei GdGfJUGQ s
(3GdfSNI HgG MhGTs
(3cJHJ HNW eged GdfbWs
(3HgG fXGe GdJYbjHIs
(3cJHJ fbdkG Yf fSNI HNW GdeDda hYdi MGTjI fSNJg gPg SeGY heYGQVI HNW GdeDda hHBNQgG SeGY SfI (B836 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN faSg hTgO GdeDda Ydi gPG GdSeGY hELGRI HNWg hUaMI GdZdGa CjVkG HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdeLGejYs